The Essence f Theo Application of Legal Justice to The Systematics of Land Registration According to Government Regulation Number 24 of 1997 - Zulfikar, Muh Reza; Habiba, Habiba (eScience Humanity Journal, 2024)
This study aims to explore the principles of legal justice that should be applied in the land registration process in Indonesia by analyzing that according to Government Regulation Number 24 of 1997 can succeed in creating a fair system for all parties. Through a qualitative approach with normative analysis, this study outlines various aspects of justice that should be reflected in the law. The results of the research, creating a fair and equitable land registration system, there are still various technical, administrative, and social obstacles that hinder the realization of the optimal application of the principle of justice. Conclusion in terms of land registration policies and practices to ensure that legal justice can be realized more effectively and equitably for all Indonesia people.